2022
DOI: 10.3390/ijerph19063712
|View full text |Cite
|
Sign up to set email alerts
|

Headache in the Workplace: Analysis of Factors Influencing Headaches in Terms of Productivity and Health

Abstract: Headache is a very common condition that can have a significant impact on work. This study aimed to assess the prevalence of headaches and their impact on a sample of 1076 workers from 18 small companies operating in different sectors. The workers who volunteered to participate were asked to fill in the Headache Impact Test-6 (HIT-6) and answer questions designed to assess stressful and traumatic factors potentially associated with headaches. The volunteers subsequently underwent a medical examination and test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 87 publications
1
23
1
Order By: Relevance
“…The WHO estimated that almost half of the adult population have had a headache at least once within the previous year [ 37 ]. Our field study confirmed that 48.8% of workers suffered from headaches, which were severe in over a third of cases; as a result, about one in five workers experienced a severe headache impact on their ability to work [ 21 ]. A Portuguese study estimated the average annual cost of each case of headache in employees to be over EUR 660 in direct costs.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…The WHO estimated that almost half of the adult population have had a headache at least once within the previous year [ 37 ]. Our field study confirmed that 48.8% of workers suffered from headaches, which were severe in over a third of cases; as a result, about one in five workers experienced a severe headache impact on their ability to work [ 21 ]. A Portuguese study estimated the average annual cost of each case of headache in employees to be over EUR 660 in direct costs.…”
Section: Discussionsupporting
confidence: 69%
“…In conclusion, this study demonstrates that violence experienced during work is associated not only with immediately visible consequences, such as physical injury, anger, fear, and other emotional phenomena, but also with neuropsychological problems such as headaches and sleep disorders that are highly insidious and may persist even several months after an attack. Headaches in the workplace have been associated with anxiety, depression, and metabolic disorders [ 21 ]. Sleep problems are significantly associated with immune and metabolic disorders, injuries, and traffic accidents [ 73 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the aforementioned limits, our study advocates a stronger collaboration between OP and professionals involved in the management of migraine in the general population [ 9 , 15 ]. In this regard, our methodology could be implemented in future studies in order to assess a broader array of neurological disorders [ 5 ], and particularly headache [ 9 ], whose overall burden deeply affects the quality of life of affected individuals, creating a long-lasting imbalance between occupational requirements and workers’ potential performances [ 9 , 36 , 54 ]. Finally, future studies should also aim to distinctively evaluate a broader array of different work settings, focusing on both specific risk factors and properly tailored preventive interventions.…”
Section: Discussionmentioning
confidence: 99%
“…As the prevalence of migraine usually increases up to 30–39 years of age, gradually decreasing afterwards [ 1 , 6 , 8 ], it affects the most productive years of an individual’s personal, social and professional development [ 3 , 9 ], overlapping with the peak of the employment years [ 10 ]. Unsurprisingly, migraine is therefore recognized as a significant cause of days of work lost and reduced quality of life [ 6 , 8 , 9 , 10 ]. In Europe, migraineur workers may lose between 27.6 and 28.8 working days per year, with consequent costs for patients, employers, healthcare systems [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%